Bankaların internet bankacılığını kullanan müşterilerinin tutumlarına ilişkin değerlendirmeleri ve bir uygulama - Umur, Kemal (My University, 2006)
BANKALARIN İNTERNET BANKACILIĞINI KULLANAN MÜŞTERİLERİNİN TUTUMLARINA İLİŞKİN DEĞERLENDİRMELERİ VE BİR UYGULAMA Günümüzdeki değişiklikler baş döndürücü bir şekilde gelişmektedir. Dijital çağ diye tanımlanan bu yeni evreye bu gelişimin en son halkası denebilir.Ekonomide küreselleşme ve bilgi teknolojilerinin gelişip yaygınlaşması ile bilgisayar ve internet aracılığı ile ileri teknoloji gerektiren yeni ekonomik aktiviteler ortaya çıkmıştır. Türkiye'de bankacılık sektöründe son yıllarda oluşan büyük değişim sonunda, klasik bankacılık ürünleri özelliğini yitirmiştir. Teknolojinin çok hızlı bir şekilde gelişmesiyle bankalar da geleneksel iş modellerini terk ederek modern bankacılık uygulamalarına yönelmişlerdir. İnternet bankacılığının banka müşterilerine kazandırdığı maliyet, hız, mobil işlem imkanı bu bankacılık kanalına olan talebi gün geçtikçe arttırmaktadır. Bilgi teknolojilerindeki bu baş döndürücü değişime Türk bankaları başarıyla ayak uydurmaktadır. İnternet teknolojilerinde meydana gelen değişimler bankacılık sektörüne çok hızlı bir şekilde yansımaktadır. Bilişim teknolojilerinde meydana gelen bu baş döndürücü yenilikler bankacılık endüstrisi için de yeni ufuklar açmaktadır. Bu çalışma Türk bankacılık sektöründe internet bankacılığı uygulamalarının gelişimini izlemek ve internet bankası müşterilerini bankalar yönünden değerlendirilmesine katkıda bulunmak amacıyla gerçekleştirilmiştir. STUDY OF THE ATTITUDES OF BANKS CUSTOMERS USING INTERNET BANKING AND AN APPLICATION Nowadays, changes are growing in a dazzling way. This new stage which is defined as Digitial Age can be called as the ultimate phase of this development. New economic activities requiring advanced technology has come out with the globalization of economy and improvement in information technology through the practice of computer and internet. In Turkey because of the major changes in banking sector at last years, classical banking products lost their characteristics. By the rapid development in technologies, banks also quit the traditional service technics and headed for modern banking application technics. The advantages that internet banking brought to the customers such as low cost, speed, opportunity of mobile transactions, increase the demand for internet banking from day to day. Turkish Banks are succesfully keeping up with this dazzling changing in information technology. The changes occuring in internet technologies is reflecting immediately banking sector. This dazzling innovations in informatics technologies also open up new frontiers to the banking industry. This study is done to contribute to view the evolution of internet banking technics in Turkey and examining the internet banking customers in the perspective of banks. In the first part of the study; the progress of internet in the world and in Turkey, the interaction between the internet and marketing is examined by giving the general information about internet. In the second part, by dwelling on the new economy concept which still has arguments going on today some information is given about internet banking and its applications. Besides, the advantages of internet banking in terms of customers and banks is emphazied as well as the internet security which is one of the most important matter. In the last part, a questionnaire about internet banking which is studied in the first two parts is done to the deposit banks in Turkey. After making a comperative research for internet banking applications, this part comes to an end with general comments and suggestions.
Keywords: İnternet_Bankalar ve Bankacılık; Müşteri Hizmetleri; Müşteri İlişkileri_Bankalar ve Bankacılık